EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE DAN TEAM ASSISTED INDIVIDUALIZATION PADA MATERI TRIGONOMETRI DITINJAU DARI MINAT BELAJAR MATEMATIKA SISWA SMK DI KABUPATEN PONOROGO TAHUN PELAJARAN 2011/2012 - Budiastuti, Siti Amirah; Mardiyana, Mardiyana; Triyanto, Triyanto (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objectives of this research are to investigate: (1) wich learning model of Think Pair Share (TPS), Team Assisted Individualization (TAI), or conventional learning model results in a better learning achievement in Mathematics, (2) which learning interest of the high learning interest, the moderate learning interest, and the low learning interest results in a better learning achievement in Mathematics,(3) in the students with the high, moderate, and low learning interests, wich learning model of Think Pair Share (TPS), Team Assisted Individualization (TAI), and conventional learning model results in a better learning achievement in Mathematics. This research used the quasi experimental research method with the factorial design of 3x3. The population of the research were the students of Vocational High School (SMK) in Ponorogo regency on Academic Year 2011/2012. The samples of the research were taken by using the stratified cluster random sampling technique. It was conducted at SMK 1 of Ponorogo, SMK Bakti of Ponorogo, and SMK Sore 1 of Ponorogo. The samples included two experimental classes and one control class of each of the schools. The size of the sample was 275 students consisted of 84 students in the first experimental class, 105 sudents in the second experimental class and 86 students in control class. The data of the research were gathered through mathematics achievement tes and quetionary of learning interest. The data was analyzed by using two-way analysis of variance with.The results of the reseach are as follows: (1) both TPS and TAI result in the same good learning achievement in Mathematics, and result in a better learning achievement than the conventional one does; (2) the students with the higher learning interest have a better learning achievement in Mathematics than those with the moderate learning interest and the low learning interest, but the students with the moderat learning interest have the same learning achievement in Mathematics those with the low learning interest; (3) in the students with the high, moderat, and low learning interest, both TPS and TAI result in the same good learning achievement in Mathematics, and result in a better learning achievement than the conventional one does.Key words: Think Pair Share, Team Assisted Individualization, Conventional, Learning Interest